2005
DOI: 10.1161/circulationaha.104.463125
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Myocardial Deformation Properties Predict Maintenance of Sinus Rhythm After External Cardioversion of Recent-Onset Lone Atrial Fibrillation

Abstract: Background-Accurate echocardiographic parameters to predict maintenance of sinus rhythm in patients with atrial fibrillation (AF) are poorly defined. This study was conducted to assess the atrial myocardial properties during AF through myocardial velocity, strain rate, and strain and to compare their prognostic value in maintaining sinus rhythm in patients with lone AF with standard transthoracic (TTE) and transesophageal echocardiography (TEE). Methods and Results-Sixty-five consecutive patients with lone AF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
206
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(222 citation statements)
references
References 37 publications
7
206
3
6
Order By: Relevance
“…[385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400] Strain (S) and strain rate (SR) imaging provide data on myocardial deformation by estimating spatial gradients in myocardial velocities. 385,388,392,393,[401][402][403][404][405] This technique has been used as a surrogate of LA structural remodelling and fibrosis. [388][389][390][391][392][393] Interestingly, LA dysfunction with changes in strain and strain rate has been observed in patients with amyloidosis in the absence of other echocardiographic features of cardiac involvement.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
“…[385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400] Strain (S) and strain rate (SR) imaging provide data on myocardial deformation by estimating spatial gradients in myocardial velocities. 385,388,392,393,[401][402][403][404][405] This technique has been used as a surrogate of LA structural remodelling and fibrosis. [388][389][390][391][392][393] Interestingly, LA dysfunction with changes in strain and strain rate has been observed in patients with amyloidosis in the absence of other echocardiographic features of cardiac involvement.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
“…17)18) In a recent study, strain/rate imaging has been proposed as strong index of the atrial reservoir function, and the degree of the impairment in atrial compliance, as assessed by strain and the strain rate, seems to be strongly predictive of maintaining sinus rhythm in patients with AF. 19) In our previous study, the lower values of strain/rate in the AF patients suggest decreased passive lengthening (stretching) and shortening of the atrial walls, and this is possibly because of atrial remodeling with fibrosis and the reduced compliance. 13) Electrical and structural remodeling AF is characterized by atrial dilatation and shortening of the atrial effective refractory period 20)21) and this may act as perpetuators, ensuring the persistence of AF for a longer period.…”
Section: Discussionmentioning
confidence: 77%
“…The results of this investigation showed agreement with a previous study that reported patients with higher atrial strain and a higher strain rate appeared to have a greater likelihood of staying in sinus rhythm. 19) The atrial biopsy specimens of AF patients have demonstrated inflammatory changes and increased fibrosis, providing evidence of the possible role of inflammation in atrial structural remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LA myocardial strain has been confirmed as a reliable index that represents the magnitude of atrial deformation [20]. E/e' ratio 10.0 ± 2.6 5.9 ± 1.8 < 0.001 E -peak early diastolic filling velocity; A -peak late diastolic filling velocity; e' -peak early diastolic velocity of the mitral annulus; a' -peak late diastolic velocity of the mitral annulus In previously published studies, global LA strain and strain rate were significantly reduced in patients with paroxysmal AF, compared with the normal control subjects [21,22].…”
Section: Discussionmentioning
confidence: 99%